GEL HAND SANITIZER OF CELERY LEAVES Apium graveolens Linn. AS ANTIBACTERIAL - Kristianingsih, Ida; Nurmalia, Ulvia; Pratama, Newi Solika; Kustiani, Nofi Ria (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2018)
ABSTRACT In this research, gel hand sanitizer formulation using celery leaves of Apium graveolens Linn has been formated. This leave is reported to have antibacterial activities due to flavonoids and tannins contained. The method used physical characteristion and antibacterial inhibition test with diffusion method. It was made from three evaluation formulas with concentration of the extract 12,5, 15 dan 20% and CMC 2% respectives. The characteristic results showed that gel hand sanitizer are semi-solid, blackish brown, celery peculiar smell, pH 5.8, distribution test 2,9 cm, load 50 gram 3 cm, 100 gram 3 cm and 150 gram 3,1 cm, homogeneous and comfortable in the skin. The results showed that gel hand sanitizer formulations 1, 2 and 3 were able to provide antibacterial inhibition. Gel with 20% extract and 2% CMC Na could reduce the number of bacteria E coli and Staphylococcus aureus. It can be concluded that gel hand sanitizer using Leaf Celery Extract Apium graveolens Linn. had antibacterial activities.